Another Reason for Vaccine Hesitancy in Turkey: Siblings with Autism Spectrum Disorder - Bayturan, Semra; Şen Celasin, Nesrin (Tropical Health and Medical Research, 2022)
Despite studies showing no link between the measles-mumps-rubella vaccine and autism spectrum disorder (ASD), the belief that the vaccine causes autism can still affect parents' attitudes towards vaccines. This study aimed to investigate the vaccination status, vaccine information source, and the factors related to vaccine hesitancy diagnosed with ASD and their younger siblings based on interviews and questionnaires. A questionnaire was performed on 37 ASD groups (parents of children with ASD and their younger siblings) and 65 control groups (families with healthy children and healthy younger siblings). The research was conducted between 1st January 2019 and 31st December 2019. Incomplete vaccination was found higher in both children with ASD(n=37) and their younger siblings compared to the healthy control group(n=65) (p=0.045; p=0.016). The four children (10.8%) diagnosed with ASD had five siblings with incomplete or missing vaccinations. Families with children with ASD stated that their knowledge of vaccines was sufficient compared to the control group (p=0.021). All parents stated the autism vaccination relationship as the reason for incomplete vaccination. Parents of children with ASD may delay or reject vaccination for their children and their younger siblings.